System of urban flood control: A Comparative Study between Kanagawa Prefecture and Makassar City. (February 2019) - Sudirman; Trisutomo, S; Barkey, R A; Ali, M; Imura, H; Onishi, A; Tsai, P; Yonezaki, K
Abstract: Flooding is a water event inundation the land area due to the overflow of water from rivers or rainwater runoffs with high intensity. Kanagawa Prefecture is a country of Japan that has overcome flood events with a simple and high-tech flood control system. The conservation of watersheds and green open spaces as water catchments and the use of naturally occurring and artificial rivers and ponds show the simplicity of the flood control technology adopted by the Kanagawa Prefecture government. Subsurface drainage is a high-tech flood control system that is connected to surface drainage and guttering system in resident's housing. Based on the Kanagawa experiences, this study is an effort to apply the concept for the Makassar City of Indonesia, which the flood still occurs. Data collection methods were conducted with direct observation in the field and were described qualitatively based on the facts and literature approaches. The results of the analysis indicate that the type of flood control such as Miyagase dam in Kanagawa prefecture is the same as the Bili-Bili dam on Jeneberang River as flood control in Makassar City. The high-tech flood control type in Kanagawa Prefecture is sub-surface drainage that has not been applied in Makassar. This research is expected to be a reference for the Government of Indonesia, especially the City of Makassar in formulating policy concerning solving the problem of flooding.